Insilico Structural Analysis and Homology Modeling of Crustin Protein from Fiddler Crab Species - J. Lokeshwari; K. Sathya; A. Nathiya; K. Shoba (International Journal of Cheminformatics, 2024)
In terms of biomass and ecological or economic importance, the crustacea are the largest, most noticeable, and possibly, the most significance group of marine or aquatic arthropods. Because of their enormous commercial value and the necessity to prevent disease outbreaks in the shellfish aquaculture industry, decapods are the experimental animals of choice for practically all biological studies involving immune responses. Antimicrobial host-defense peptides (AMPs) are major components of metazoan immunity, especially for invertebrates that lack adaptive immune system. In addition to the quick and effective neutralizing action against invading microorganisms (e.g. Gram-positive and Gram-negative bacteria, yeast, filamentous fungi and enveloped viruses), these natural antibiotics may by play multifunctional roles in host-pathogens interaction by regulating important components of immunity upon infections. Antimicrobial protein crustin sequences from species of fiddler crab were obtained in FASTA format from the NCBI database. Structural and functional investigations of antimicrobial protein fiddler crabs are predicted to have a broad range of medical applications in the future. Procheckonline software was also used to give us the verification of the structure obtained.
Keywords: AMP; Bioinformatics; Crustacea; Crustin; NCBI; Rapper; fiddler crab